Programmable and robust static topological solitons in mechanical metamaterials - Yafei Zhang; Bo Li; Q. S. Zheng; Guy M. Genin; C. Q. Chen (Nature Communications, 2019)
Mechanical solitons are notoriously difficult to control. Here, the authors report a theoretical framework for programming static periodic topological solitons into a metamaterial, and demonstrate its implementation in real metamaterials computationally and experimentally.